2006
DOI: 10.5713/ajas.2007.252
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vitamin E and Vitamin C on the Performance of Japanese Quails (Coturnix Coturnix Japonica) Reared under Heat Stress during Growth and Egg Production Period

Abstract: This study was carried out to determine the effect of vitamin E and vitamin C on the performance of Japanese quails (Coturnix coturnix japonica) reared under heat stress during the growth and egg production period. A total of 810 seven-day-old Japanese quails were used in the trial. The birds received a diet with either three levels of vitamin E (DL-α Tocopheryl acetate) (60, 120 and 240 mg/kg of diet) and vitamin C (ROVIMIX STAY-C 35) (60, 120 and 240 mg/kg of diet). Live weight on day 35 and weight gain were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
5
33
2
3
Order By: Relevance
“…During environmental stress, the serum and tissue level of vitamin E decreases; thus, supplementation of vitamin E is beneficial (Ipek and 2014). Secondly, poultry cannot synthesize vitamin E, unlike vitamin C, and therefore it must be added to the diet Ipek and Dikmen, 2014). In the present study, the inclusion levels of vitamin E had no significant effect on the performance traits of quails reared under low ambient temperature.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…During environmental stress, the serum and tissue level of vitamin E decreases; thus, supplementation of vitamin E is beneficial (Ipek and 2014). Secondly, poultry cannot synthesize vitamin E, unlike vitamin C, and therefore it must be added to the diet Ipek and Dikmen, 2014). In the present study, the inclusion levels of vitamin E had no significant effect on the performance traits of quails reared under low ambient temperature.…”
Section: Discussionmentioning
confidence: 49%
“…Previously, improved performance in poultry has been reported under higher doses ranging from 250 to 500 mg/kg. Improved body weight, digestibility, and carcass characteristics have been documented in Japanese quail under environmental heat stress (Sahin and Kucuk, 2001;Ipek and Dikmen, 2014). Sahin et al (2003a) reported improved body weight, dry matter intake, FCR, and egg production when vitamin E was supplemented at the level of 250 mg/kg of feed in Japanese quail under cold stress condition (6 °C).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations